A phase I, randomized, proof‐of‐clinical‐mechanism study assessing the pharmacokinetics and pharmacodynamics of the oral PDE9A inhibitor BI 409306 in healthy male volunteers. (January 2017) - Boland, Katja; Moschetti, Viktoria; Dansirikul, Chantaratsamon; Pichereau, Solen; Gheyle, Lien; Runge, Frank; Zimdahl‐Gelling, Heike; Sand, Michael
Abstract: Objective: Cyclic guanosine monophosphate (cGMP)‐specific phosphodiesterase (PDE) inhibitors are hypothesized to improve cognition in schizophrenia and Alzheimer disease by increasing cGMP levels in certain brain regions. This phase I, randomized, parallel‐group, double‐blind, placebo‐controlled study provides proof‐of‐mechanism evidence for BI 409306, a novel, oral PDE9A inhibitor. Methods: In healthy males, exposure of BI 409306 (25‐, 50‐, 100‐, and 200‐mg single dose) and placebo was assessed in plasma and cerebrospinal fluid (CSF). Effect of BI 409306 on CSF cGMP levels was evaluated, and adverse events (AEs) were monitored. Results: In all enrolled subjects ( N  = 20), plasma BI 409306 concentration increased rapidly (median tmax : 0.75–1.25 hr) followed by rapid increases in CSF (median tmax : 1.5–2.0 hr). Maximum CSF cGMP concentrations were achieved within 2 to 5 hr, declining to baseline levels 10 to 14 hr after dosing. Dose‐dependent increases in plasma and CSF exposure and CSF cGMP were shown. BI 409306 was safe and well tolerated. Most AEs were mild to moderate in intensity and study procedure–related. Conclusions: BI 409306 increased rapidly in plasma and was subsequently detected in CSF, resulting in dose‐dependent increases in cGMP levels in CSF. Results indicate BI 409306 efficiently crosses the blood‐CSF barrier, with an acceptable level of AEs.